50 A Cross-Sectional Study Examining the Association Between MRCS Performance and Surgeons Receiving Fitness to Practice Sanctions. (12th October 2021) - Ellis, R; Scrimgeour, D; Cleland, J; Lee, A; Brennan, P
Abstract: Aim: Fitness to practice (FtP) investigations by the General Medical Council (GMC) can be one of the most stressful experiences in a surgeon's career. Demographic factors are known to alter the likelihood of GMC investigation. Despite this there are no studies assessing risk factors in surgeons for FtP sanctions. Thus, we used the newly created Intercollegiate Membership of Royal College of Surgeons (MRCS) examination database to identify risk factors for and the prevalence of GMC sanctions in early-career surgeons. Method: FtP sanction data contained in the GMC list of registered medical practitioners (LRMP) database was linked at person-level to all UK graduates who had attempted MRCS Part A or Part B between September 2007 and January 2020. Data were anonymised by the Royal College of Surgeons of England prior to analysis. Results: f 11, 660 candidates who had attempted the MRCS within the study period only 31 (0.3%) candidates had GMC FtP sanctions within the last two years. Of these, 12 had active conditions on their registration, 7 had active undertakings and 14 had warnings. Candidate demographics were similar between cohorts and there were no significant differences between MRCS performance identified. Conclusions: In this, the largest study of MRCS candidates to date, the prevalence of active FtP sanctions in early-career surgeons was 0.3%, significantly lower than the prevalence of sanctions across more experienced UK surgeons (0.9%). These data highlight early-career surgeons as a low-risk group for disciplinary action and should reassure patients and medical professionals of the rarity of FtP sanctions.